State management on order security in the background Industrial revolution 4.0 - PhD. Ta Thanh Huong, PhD. Ta Thanh Huong, PhD. Nguyen Thanh Dong, MA. Vu The Cong, (International Journal of Advanced Science and Technology, 2020)
Along with the process of international integration, the development of information technology, especially the 4.0 technology revolution, the reality, the situation taking place in internet space; that have set an urgent requirements for public network security in national security protection, ensuring social order and safety. In this research, the author generalized the role and meaning of science and technology 4.0 for the socio-economic development in general and the impact on state management on security and security in particular. Especially, this research also points out the negative impacts on the security and order situation of the 4.0 technology revolution, therefore giving some solutions to improve the efficiency of State management on Security in Vietnam in the context of the 4.0 technology revolution today.